BREEDING FOR TOLERANCE TO SALT STRESS IN RICE USING A NEW TOLERANCE DONOR, MADINA KOYO - AMOAH, NANA KOFI ABAKA (KNUST, 2025)
Salt stress is a major constraint that reduces productivity of many rice fields across the world. Susceptibility of the crop comes within the first few weeks of establishment and later during the reproductive stage. Many studies conducted to improve the adaptability of the crop to saline soils has focused on introgression alleles from a few donor genetic background. To broaden the genetic base of tolerant alleles, a new salt stress donor cultivar, “Madina Koyo” was used in developing a set of introgression lines with a farmer preferred indica variety, „Sahel 317‟. To identify lines that are tolerant to the stress at the two most susceptible stages, F2 derived F3 lines (F2:3) and F3:4 lines were evaluated at the early seedling and reproductive stages respectively. To better understand the regions controlling tolerance in this new donor and to validate previously reported regions, QTL mapping was undertaken using Single Nucleotide Polymorphism (SNP) analysis from Genotype by sequencing (GBS). Salt stress caused a drastic reduction of 72% in grain yield among the F2:3 progenies. Altogether, an average reduction of 63.4% was observed for all fitness related traits among selected F3:4 progenies at the early seedling stage. A total of 45 progenies had better or comparable grain yield to the donor parent “Madina Koyo” and were adjudged to be tolerant at the reproductive stage. Subsequently, another 46 progenies, representing 5% of the evaluated progenies, recorded an average SES score 1-3 and were rated as tolerant to salt stress at the early seedling stage. Out of the combined 91 progenies, only one progeny, ARS1181-1-6-27, was observed to be tolerant to salt stress at both growth stages. Another four progenies (ARS1181-1- 7-6, ARS1181-1-6-6, ARS1181-1-8-26 and ARS1181-1-10-1) combined tolerance at the seedling stage with better yield stability. These five promising progenies should be further evaluated with the aim of releasing as per se or be used as parents in future iii forward breeding efforts. A high-density genetic linkage map was constructed for the 12 rice chromosomes using 3698 SNP markers. Composite interval mapping identified 46 QTLs on 10 chromosomes (1, 2, 3, 4, 7, 8, 9, 10, 11 and 12) for SES, shoot length, shoot dry weight and root dry weight. No QTL was identified for root length. Thirty three out of the 46 QTLs were shoot-related QTLs while five were root related. Breeders should, therefore, focus on shoot related traits when evaluating rice germplasm for salt tolerance at the seedling stage. None of the QTLs identified was mapped in the region of previously reported major effect QTL Saltol on chromosome 1, suggesting that Madina Koyo controls tolerance from a different region by a different QTL(s). Six out of the 46 (qSDW1.1, qSDW2, qSL1.1, qSL2.2, qSL2.3 and qSL2.4) were major effect QTLs with phenotypic contributions ranging from 11% - 99%. Comparison with literature suggests the novelty of these major effect QTLs. Fine mapping of these novel QTLs in a different genetic background is necessary to confirm their stability and use in breeding to enhance the level of tolerance through MAS for the pyramiding of different QTLs to one genetic background